PSYCHOLOGICAL CONCEPT OF HEALTH AND "NORM" - Ergasheva Nargiza (Journals Park Publishing, 2022)
In this article we talked about psychological health, mental health, the concepts of “harmony”, “norm”, common sense and morality, adaptability to social life, personal optimism, emotional, interpersonal relationships.
Keywords: covert management; technology; information flow